Did COVID-19 risk perceptions influence the handwashing behavior of the Filipino population? - V. Labana, Ryan; E. Cruz, Mhelorie Kesia; M. Ramirez, Abdul Abbu Jamaila; E. Raya, Marie (International Journal of Public Health Science (IJPHS), 2024)
The COVID-19 pandemic reminded people of the importance of proper handwashing. The degree of health risk perceptions and handwashing behavior during the COVID-19 pandemic opens essential lessons for delivering water, sanitation, and hygiene (WASH) programs across the globe. We measured the relationship between COVID-19 risk perception and the handwashing behavior of 386 Filipinos in a highly urbanized city in the Philippines. Self-made COVID-19 risk perception scale (CRPS) (Cronbach's α 0.93) and handwashing behavior scale (HBS) (Cronbach's α 0.84) were administered face-to-face. The results show that the overall handwashing behavior has a median of 4.1 (frequently), while the interquartile range (IQR) is 0.5. Regression analysis revealed that COVID-19 risk perception has a significant positive association with overall handwashing behavior (B=0.369, p-value <0.05). The COVID-19 risk perception accounts for 36.9% of the variance in handwashing behavior, F (1, 384) =11.6360, p-value=0.0007. This study proposes that public health authorities target people's experiential learning style in designing and delivering intervention programs against non-compliance with proper handwashing.